Belminus ferroae n. sp. from the Colombian north-east, with a key to the species of the genus (Hemiptera: Reduviidae: Triatominae) - Sandoval, Claudia Magaly; Pabón, Eulides; Jurberg, José; Galvão, Cleber (Zootaxa, 2007)
Belminus ferroae, a new triatomine species, is described on the basis of specimens collected in dwellings of the Andean oriental mountain range, municipality Toledo, Departament of North Santander, Colombia. It differs from other species of the genus in the color pattern of the body, corium light colored, cells of the membrane light brown, with secondary venation that gives a reticular aspect to the wing, in design of the connexivum, and phallic structures of the male. Illustrations of male genitalia of Belminus herreri, a related species, are included.